The effect of mint oil on nausea and vomiting during pregnancy - Suci Santika Putri; Nurul Isnaini; Ike Ate Yuviska (Malahayati International Journal of Nursing and Health Science, 2020)
Background: Base on data in Lampung-Indonesia in 2017 of 182,815 pregnant women in the first trimester pregnancy, recorded a high number of emesis gravidarum by 50-90%, while hyperemesis gravidarum reached 10-15%.Purpose: To know the effect of mint oil on nausea and vomiting during pregnancyMethods: A quantitative research by pre-experimental research design (one group pretest posttest). The population was pregnant women in the first trimester  complain of nausea and vomiting of 36 pregnant women taken by total sampling and by criteria inclusion found of 30 pregnant women. Univariate data analysis which presents the percentage of pappermint administration to reduce nausea and vomiting in pregnant women. Bivariate analysis proves the hypothesis whether there is an effect of pappermint oil aromatherapy to reduce nausea and vomiting of pregnant women by statistical test used is the T-test.Results: The average a complain of nausea and vomiting in pregnant women before being given aromatherapy pappermint oil it was 17.50 and after being given aromatherapy pappermint oil it was 10.60. Effect of aromatherapy pappermint oil to reduce of nausea and vomiting in pregnant women (p-value 0,000 <α 0.05).Conclusion: There was effect of Aromatherapy Pappermint Oil to reduce of nausea and vomiting in pregnant women. It is recommended  to pregnant women who experience of nausea and vomiting can be treated with alternative therapy by aromatherapy peppermint which has been proven to reduce nausea and vomiting.